2018
DOI: 10.1002/1873-3468.12972
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of neuronal development and function by ROS

Abstract: Reactive oxygen species (ROS) have long been studied as destructive agents in the context of nervous system ageing, disease and degeneration. Their roles as signalling molecules under normal physiological conditions is less well understood. Recent studies have provided ample evidence of ROS‐regulating neuronal development and function, from the establishment of neuronal polarity to growth cone pathfinding; from the regulation of connectivity and synaptic transmission to the tuning of neuronal networks. Appreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(130 citation statements)
references
References 138 publications
(197 reference statements)
4
124
0
2
Order By: Relevance
“…According to many studies that support the link between exposure to an adverse intrauterine milieu, including hyperglycemia, and a subsequent risk of developing metabolic diseases [3,9,[50][51][52], our results show a metabolic disruption in male and female GD offspring. The male progeny only showed modifications in lipid metabolism in adulthood, whereas in female offspring, we observed an increase in the insulin level, indicative of insulin resistance, and a lipid metabolism alteration at both ages, indicating a sex-dependent metabolic disruption.…”
Section: Discussionsupporting
confidence: 69%
“…According to many studies that support the link between exposure to an adverse intrauterine milieu, including hyperglycemia, and a subsequent risk of developing metabolic diseases [3,9,[50][51][52], our results show a metabolic disruption in male and female GD offspring. The male progeny only showed modifications in lipid metabolism in adulthood, whereas in female offspring, we observed an increase in the insulin level, indicative of insulin resistance, and a lipid metabolism alteration at both ages, indicating a sex-dependent metabolic disruption.…”
Section: Discussionsupporting
confidence: 69%
“…Glutamate stimulation is known to prompt ROS production in a Ca 2+ -dependent manner 26 , and ROS are known to mobilize Zn 2+ from cytosolic metallothioneins 2729 , although whether the minimum timescale of this mobilization matches our observations is unclear. Some research has shown that ROS may be involved in physiological responses 30 , so ROS-dependent Zn 2+ mobilization may not necessarily be indicative of oxidative stress. Furthermore, 60 mM KCl has been shown to not produce intracellular ROS 27 , thus potentially explaining the limited extent of the Zn 2+ signal we observed upon KCl stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the NMDA-type receptors hyperactivation also results in glutamate-induced excitotoxicity that can lead to neuronal necrosis [24]. Finally, OS generated through Aβs can also activate stress kinases such as c-Jun N-terminal kinases (JNK), [25]. The high-affinity of Aβs for copper (Cu) and zinc (Zn) may also explain the formation of an oxidative microenvironment.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%